การตรวจสอบความเป็นสารปอซโซลานของเถ้าแกลบผสมเถ้าลอยโดยวิธีการบ่มเร่งกำลัง - ดำรงศีล สาโรจน์ (RMUTP Research Journal Sciences and Technology, 2018)
This paper presents the investigation of pozzolanic reaction of rice husk ash blended with fly ash by accelerated curing. The compressive strength of cement paste containing rice husk ash blended with fly ash at 30% by weight of cementitious material (PBA-30) was studied. The temperature curing at 60, 70 and 80 °C were parameter of test in order to determine the suitable temperature and curing period on strength development of cement paste. The ratio of rice husk ash to fly ash was 1:1 by weight and the ratio of water-to-binder (w/b) was 0.38. The test results found that the accelerated curing of PBA-30 at temperature of 60 °C for 5, 10 and 45 hours had comparable compressive strength to PBA-30 with normal curing at the age of 3, 7, and 28 days, respectively. As a result of accelerated curing, the calcium silicate (CS) which effect on strength development of cement paste was increased. According to the X-ray diffraction analysis, the calcium silicate content in cement paste was comparable. Therefore, it can be use accelerated curing to investigate the poozolanic reaction of rice husk ash blended with fly ash within 48 hours.